Numerical Simulation of Effects of River Reconstruction on Flooding: A Case Study of the Ba River, China - Haixiao Jing; Yongbiao Lang; Xinhong Wang; Mingyang Yang; Zongxiao Zhang (Advances in Materials Science and Engineering)
The local reconstruction of river channels may pose obstacles of flood flow, local eddy currents, or high flow velocity which pose potential threats to human life and infrastructures nearby. In the design of such projects, the effects of local reconstruction of the river channel on flooding are often evaluated by the one-dimensional method, which is based on the formula of one-dimensional nonuniform flow. In this study, a two-dimensional hydrodynamic model based on shallow water equations is employed to investigate the impacts of river reconstruction on flooding in the Ba River, China. The finite volume method and an unstructured triangular mesh are used to solve the governing equations numerically. The numerical model is validated by comparison with the results of a physical model of 1 : 120 scale. The backwater effects and impacts of flood flow fields under two flood frequencies are analyzed by comparing the numerical results before and after local reconstruction. The results show that the backwater length under both 10-year and 100-year floods can be reached up to the upstream boundary of the computational domain. However, the maximum water level rises are limited, and the levees in this river channel are safe enough. The flow velocity fields under both floods are changed obviously after local reconstruction in the Ba River. Areas with the potential for scour and deposition of the river bed are also pointed out. The findings of this study are helpful for the evaluation of flood risks of the river.